2011
DOI: 10.1021/jf104237y
|View full text |Cite
|
Sign up to set email alerts
|

Fast Extraction and Dilution Flow Injection Mass Spectrometry Method for Quantitative Chemical Residue Screening in Food

Abstract: A prototype multiresidue method based on fast extraction and dilution of samples followed by flow injection mass spectrometric analysis is proposed here for high-throughput chemical screening in complex matrices. The method was tested for sulfonylurea herbicides (triflusulfuron methyl, azimsulfuron, chlorimuron ethyl, sulfometuron methyl, chlorsulfuron, and flupyrsulfuron methyl), carbamate insecticides (oxamyl and methomyl), pyrimidine carboxylic acid herbicides (aminocyclopyrachlor and aminocyclopyrachlor me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Similar methods are now used in many nationwide neonatal screening programs [23,24]. In the fields of pesticide determination [25,26,27], therapeutic drug monitoring [28] and analysis of adulterated dietary supplements [29], FIA-MS/MS has recently been presented as an adequate alternative to LC-MS/MS. For FIA-MS/MS the mass spectrometer is directly coupled to a pump delivering a continuous flow of eluent solvents, whereas the LC column compartment is bypassed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar methods are now used in many nationwide neonatal screening programs [23,24]. In the fields of pesticide determination [25,26,27], therapeutic drug monitoring [28] and analysis of adulterated dietary supplements [29], FIA-MS/MS has recently been presented as an adequate alternative to LC-MS/MS. For FIA-MS/MS the mass spectrometer is directly coupled to a pump delivering a continuous flow of eluent solvents, whereas the LC column compartment is bypassed.…”
Section: Introductionmentioning
confidence: 99%
“…The two most important analytical challenges of FIA-MS/MS are: (1) assessment and exclusion of coelution bias, which is here addressed by qualifier ion monitoring [29,30], and (2) correct quantification in the presence of significant ion suppression, which is best achieved by using properly matched stable isotope-labeled internal standards (SIL-IS) [31]. If properly applied, FIA-MS/MS provides high precision, short run times and remarkable cost savings due to elimination of time-consuming and possibly error-prone procedures of sample cleanup and pre-separation [27]. …”
Section: Introductionmentioning
confidence: 99%
“…Because EI‐LC‐MS with SMB has no matrix related ion suppression effects, it does not always require LC for sample separation from the matrix, and thus a new approach is enabled for achieving ultra‐fast flow injection (FI) EI‐MS‐MS with SMB analysis. Recently, the topic of flow injection MS‐MS as an alternative to lengthy LC‐MS analysis received significant attention in the world of pesticides analysis in agricultural products …”
Section: Results—cold Ei Mass Spectra Features and Selected Applicatmentioning
confidence: 99%
“…The dominant groups of chemical constituents considered characteristic of black cohosh are the triterpene glycosides, such as 23-epi-26-deoxyactein and cimicifugoside H-1, and the polyphenols [18][19][20]. Recent pharmacological studies of black cohosh have shown that it has estrogen-like, dopaminergic, and serotonergic activity [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%